(untitled) (General Chemistry Journal, 2024)
This research aims to determine student learning outcomes after implementing the PBL learning model and emotional intelligence at SMA Negeri 1 Tompaso This type of research is quantitative with a quasi experimental approach The research population was all class Xl students of SMA Negeri 1 Tompaso totalling 167 people The research sample was determined using a random sampling technique of 60 people The instrunents used in this sheets and emotional intelligence questionnaires Data analysisnormality tests homogeneity tests and hypothesis tests namely t tests f tests and n gain The results of the research prove that the application pf the PBL learning model is quite effective in improving student learning outcomes as evidenced by the t test the mean pre test value is 56 03 and pos test 87 40 it can be seen that the post test value is greater than the pre test wit a significance of 0 000 meaning that H0 < sub>is accepted and H1 < sub>is rejected Students emotional intelligence improves student learning outcomes the results of the f test with SPSS show an fcount value of 8 184 with a significance 0 008 lt;0 05 so emotional intelligence improves student learning outcomes< em>< p>